EXPERIMENTAL VIDEO AND CREATIVE PROCESSES WITH ARTIFICIAL INTELLIGENCE: Some works by Ben Bogart - Sarzi-Ribeiro, Regilene [UNESP]; Sedeno-Valdellos, Ana (Upv-ehu Press, Serv Editorial, 2024)
Artificial intelligence (AI) has revolutionized many social and human spheres, but audiovisual creation is a central aspect in the reflection on its potential. The work focuses on some transformations that the creative process undergoes in video art or experimental video, through some works, with which one can reflect on the aesthetic dimensions, temporality, the relationship between sound and image and the ephemeral constitution of audiovisuality. The paper carries out an exploratory study on the topic with a qualitative research methodology, for the interpretation and discussion of the works-examples of the author Ben Bogart. Final considerations point out that AI includes artistic operations related to previous avant-garde media art, such as collage or appropriation. All of these tools carry numerous ethical implications and positions of the artist, as well as possibilities to subvert creative logics.
Keywords: EXPERIMENTAL VIDEO; GENERATIVE ARTIFICIAL INTELLIGENCE; VI- DEART; CREATION IN VIDEO